A review of Soaresia H. Soares, 1945, with the description of a new species from Serra da Mantiqueira, Brazil (Opiliones, Gonyleptidae, Pachylinae) - Kury, Adriano B. (Zootaxa, 2008)
Soaresia forficula sp. nov. is described from the Mantiqueira Mountain Range, Minas Gerais State, southeastern Brazil. The genus Soaresia H. Soares, 1945 previously included only Soaresia uncina H. Soares, 1945, hitherto recorded only from the type locality, Penedo, Rio de Janeiro State, in the same mountain range. A second record of S. uncina is given from a nearby locality, Serrinha do Alambari. The combined distribution of the species of Soaresia is restricted to elevations between 700 and 1300 m, in the Tropical & Subtropical Moist Broadleaf Forests biome. An emended diagnosis of the genus is given and complements are given to the description of S. uncina, including the first illustrations and description of the male genitalia.